Copy-number variations in adult patients with chronic immune thrombocytopenia - Yücesan, Emrah; YÜCESAN, EMRAH; Ng, Ozden Hatirnaz; Yalniz, Fevzi Firat; Yilmaz, Hulya; Salihoglu, Ayse; Sudutan, Tugce; Eşkazan, Ahmet Emre; Ongoren, Seniz; Baslar, Zafer; Soysal, Teoman; Ozbek, Ugur; et al. (My University, 2020)
Objectives Immune thrombocytopenia (ITP) is an autoimmune disease with heterogeneous background. FCGR2C mutations were defined in one third of the patients but genetic players have not been fully elucidated yet. Although childhood ITP present as benign, ITP in adulthood is chronic disease with treatment challenges. This study aimed to focus on adult ITP patients using a whole genome genotyping that is valuable approach to identify the responsible genomic regions for the disease. Methods Herein 24 adult primary-refractory for ITP patients were evaluated using HumanCytoSNP12BeadChip,Illumina. Forty-six age and sex matched healthy individuals, and ptients awith nonhematological conditions were analyzed as controls. Identified CNV regions were verified by qRTPCR. T-cell receptor beta and delta (TCRB/TCRG) clonality were assessed by heteroduplex analysis in mosaic cases. Results Several CNV losses and gains were defined (losses:2q,7q,17q,19p, and gains: 1q,2p,3q,4q,7q,10q,12p,13q,14q,15q,17p,20q,21p,22q,Xp). Mosaic changes of different sizes (0.2-17.77Mb) were identified in five patients and three of them showed clonality. CNV regions that were unique to ITP patients were identified for the first time and among these genes, those related to immune regulation, and cellular trafficking were noteworthy. Conclusion: Identified CNV regions harbor several candidate genes, the functions of which might shed light on the pathogenesis of chronic ITP.
Keywords: Immune thrombocytopenia; Clonality; Copy-number variation; Single nucleotide polymorphism; Whole-genome genotyping